Does Supervisory Behavior and Support Lead to Teacher’s Affective Commitment? (Global Journal of Human-Social Science, 2019)
To meet the demand of globalization war of diversity talent and fast technological developments in order to deploy and preserve an innovative workforce specifically in education industry should allow a greater amount of flexibility and innovation in their HRM policies and practices Furthermore Indian universities are presently grappling with the shortage of teachers Therefore it is imperative for universities to retain develop and improve the performance of their existing educators The central role Human Resource Management HRM practices play in creating and maintaining employee s affective commitment is critical especially in a highly socially interactive job of teaching HRM is seen as a mechanism that nurtures social relationships in order to support an innovative workforce and enlarge the innovation capacity of organizations
Keywords: supervisory behavior and support (SVBS); affective commitment and job satisfaction